Clearing Systems of Central and Eastern Europe, waiting for the TARGET2 Securities - Andrea Kriskó (European Regional Science Association (ERSA), 2014)
Clearing Systems of Central and Eastern Europe, waiting for the TARGET2 Securities I investigate the clearing systems in Europe, and try to assess the condition of clearing houses before the launch of TARGET2 Securities. I examine the levels of development in the different regions, looking at how we can interpret the core-periphery relationship. I give an overview of the ancillary systems and I examine which of these could provide a basis for the operation of TARGET2 Securities. I also reflect on the kinds of clearing practices prevalent today in areas outside the EU. I try to summarize the significance of the first connection wave, why and how the countries follow each other. How is it possible that Euroclear, the most famous clearing house only step is only planning to enter the system in a second wave, although it plays a central role in the European settlement processes? I assess whether the countries left out have to face a lag or real separation, or it is a simple ancillary way to join to the whole European system. Another very interesting question is whether joining the T2S is a real choice, or growing up to the European financial system is a necessary process. I make a detour in the direction of the characteristics of the Polish, Czech and Hungarian clearing systems, I show the settlement activity of Bulgaria and Albania. I will discuss desires, hopes and visions, the possible advantages of the new settlement platform, the factors and ideas that have promoted the process of joining T2S. I examine adaptive strategies that were created to offset the impact of the crisis. I shed light on whether globalization exerts pressure in the direction of clearing houses becoming universal, or specialization and fighting for a market gap will continue. Which fileds are unexploited? How can we find growth potential? Can the cheap labour force and Internet-based communication abolish the geographic differences? Is it all the same where we operate a clearing house? By any chance can we see an Americanization process in the clearing sector? (SWIFT-roots, English correspondence standards, common language for work, first of all English) To answer these questions, first of all I use the clearing house announcements and operating documents and I accomplish secondary statistical analysis using historical databases.
Keywords: G21; 330; TARGET2 Securities; clearing houses; financial standards